1999
DOI: 10.1007/bf02478898
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the multidrug-resistance P-glycoprotein (Pgp, MDR-1) by endothelial cells of the neovasculature in central nervous system tumors

Abstract: To elucidate the expression of the MDR1 gene products P-glycoprotein (Pgp) in endothelial cells of newly formed blood microvessels in brain tumors, 30 brain tumors were examined by immunohistochemistry using an anti-Pgp monoclonal antibody, JSB-1. Positive reactions for JSB-1 were detected in endothelial cells in newly formed microvessels in all 16 cases of glioma but not in the 4 meningiomas. Although endothelial cells in newly formed microvessels of all 10 metastatic carcinomas showed positive reactions, neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 19 publications
6
18
1
Order By: Relevance
“…32) Pgp was expressed in the tumor cells but not in the endothelial cells of four cases of meningiomas. 30) Pgp and other types of drug resistance-related gene, such as multidrug resistance-associated protein (MRP) and O 6 -methylguanine-DNA methyltransferase, are highly expressed in meningiomas. 7,10,14,34,36) Our study revealed that Pgp was expressed in 14 of 21 (66.7%) meningiomas, MDR-1 mRNA in eight of 11 (72.7%) meningiomas, and that the RI of 99m Tc-MIBI SPECT was correlated significantly with both Pgp and MDR-1 mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32) Pgp was expressed in the tumor cells but not in the endothelial cells of four cases of meningiomas. 30) Pgp and other types of drug resistance-related gene, such as multidrug resistance-associated protein (MRP) and O 6 -methylguanine-DNA methyltransferase, are highly expressed in meningiomas. 7,10,14,34,36) Our study revealed that Pgp was expressed in 14 of 21 (66.7%) meningiomas, MDR-1 mRNA in eight of 11 (72.7%) meningiomas, and that the RI of 99m Tc-MIBI SPECT was correlated significantly with both Pgp and MDR-1 mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…21,28,31) Hydroxyurea may inhibit the growth of meningioma cell lines through an apoptotic mechanism. 30) Interestingly, in vitro exposure of renal cancer cells to low-dose hydroxyurea causes loss of chromosomal aberration, decrease in the number of MDR-1 gene copies, and increased sensitivity to vinblastine. 13) Our findings indicate that 99m Tc-MIBI SPECT, although not useful to determine the proliferative potential, could predict whether meningiomas, especially recurrent or unresectable meningiomas, overexpress Pgp or MDR-1 mRNA which may be an important factor in the sensitivity or resistance to anticancer drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells can have a relatively high P-gp expression already under physiologi-cal conditions, which correspond to its manifold metabolic and protective tasks within the blood-brain barrier [36][37][38][39][40]. In glioblastomas, the newly formed vessels express high amounts of P-gp [41].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies show overexpression of the Pgp in brain tumor samples, as well as in brain-derived cell lines [6,7,8,9,10,11,12,13]. These studies used different methods to evaluate MDR-1 gene expression, such as immunohistochemistry, Western and Northern Blotting and RT-PCR.…”
Section: The Mdr-1 Gene and The Pgpmentioning
confidence: 98%